Writing extra : - Palmer, Graham (Cambridge copy collection)
Writing Extra contains a bank of imaginative photocopiable materials designed for young adults (16+) and adults. There are over 50 easy-to-prepare activities at elementary, intermediate and upper-intermediate level. The material offers teachers a refreshing approach to 18 familiar topics and can be used to supplement existing coursebooks. Students are led step-by step to a definite written outcome through a range of motivating activities such as role-plays, discussions, games and text-analysis. Each activity provides a meaningful context for real-world writing tasks such as writing e-mails, reports, letters, CVs and diaries. This book encourages students to look at the process of writing, thus developing their awareness of structure, content and the audience they are writing for